2016
DOI: 10.1007/s12072-015-9673-6
|View full text |Cite
|
Sign up to set email alerts
|

Microwave ablation of hepatocellular carcinoma with portal vein tumor thrombosis after transarterial chemoembolization: a prospective study

Abstract: Chinese Clinical Trial Register (ChiCTR): ChiCTR-ONC-12002689.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Dynamic changes of NLR had independent prognostic significance (p = 0.035) in HCC with portal vein tumour thrombosis treated by microwave ablation after transarterial chemoembolisation [60]. In 506 patients treated by thermal ablation of recurrent HCC, high pretreatment NLR (≥2.14) was a prognostic factor for recurrence-free survival, confirmed by…”
Section: Neutrophil-to-lymphocyte Ratio In Hcc Patients Undergoing Tumentioning
confidence: 76%
“…Dynamic changes of NLR had independent prognostic significance (p = 0.035) in HCC with portal vein tumour thrombosis treated by microwave ablation after transarterial chemoembolisation [60]. In 506 patients treated by thermal ablation of recurrent HCC, high pretreatment NLR (≥2.14) was a prognostic factor for recurrence-free survival, confirmed by…”
Section: Neutrophil-to-lymphocyte Ratio In Hcc Patients Undergoing Tumentioning
confidence: 76%
“…In patients with vascular/biliary tumour thrombosis, the thrombosis was treated via thermal ablation. Specific ablation procedures for tumour thrombosis have been reported in previous papers [18,37].…”
Section: Patients and Tumour Characteristicsmentioning
confidence: 99%
“…Combination therapy with MWA after TACE may provide a substantial benefit for patients with HCC who have portal vein thrombosis (PVTT) and Child-Pugh class A or B. 35 In one study, while MWA and RFA, when combined with neoadjuvant TAE or TACE, had similar safety and efficacy profiles in the treatment of early-stage HCC, TACE/TAE and MWA provided more durable disease control in this study when compared with TACE/TAE and RFA. 36 A separate study found that MWA plus TACE is a safe, feasible, and effective therapy in the treatment of 5 to 10 cm HCC in patients with cirrhosis.…”
Section: Combined Tace and Microwave Ablationmentioning
confidence: 65%